The Use of Personification in the Lyrics of Erkin Vahidov - Komila, Komiljonova (European Journal of Life Safety and Stability (2660-9630), 2023)
Theories about poetic art appeared several centuries ago. First they were studied by Arab and Persian scientists, and then by Turkish scientists. These arts are divided into two types: poetic arts related to the meaning of the word and poetic arts related to the form of the word. Some scientists say that there is a third type, which includes both meaning and form. This article presents theories about the art of personification and its origin. And this art was studied on the basis of "Devon of Youth" by Erkin Vakhidov. Examples from "Devon" are taken and analyzed. The role of personification in the expression of meaning is also explained.